The Influence of Intellectual Capital and Sustainability Reports on Company Value with Profitability as an Intervening Variable (Empirical Study of Manufacturing Sector Companies Listed on the Indonesian Stock) - Siti Aisyah; Wiwik Utami (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
This research aims to examine the Influence of Intellectual Capital and Sustainability Report Disclosure on Company Value with Profitability as an Intervening Variable (Empirical Study of Manufacturing Sector Companies Listed on the Indonesia Stock Exchange in 2019-2021)”. Sampling was carried out using the random sampling method. The number of samples used in this research was 198 samples from 66 companies. The data analysis technique was carried out using path analysis. Research results show that Intellectual Capital has a significant effect on Profitability, the Sustainability Report has no significant effect on Profitability, Intellectual Capital has a significant effect on Firm Value, the Sustainability Report has a significant effect on Company Value, Profitability has a significant effect on Firm Value, Profitability as an intervening variable can’t mediate the influence of Intellectual Capital on Company Value, and Profitability as an intervening variable can’t mediate the influence of Sustainability Reports on Company Value.